Product development through design for assembly (DFA) and theory of inventive problem solving (TRIZ) methodologies of electric barbeque grill - Basharudin, Ilyas Tufail (2014)
Design for Assembly (DFA) is an approach to simplify the product through reducing number of parts by eliminating or merging the particular parts. Meanwhile, Theory of Inventive Problem Solving (TRIZ) is a systematic tool that enhances the decision making through systematic procedure either than trial-and-error method. This project report describes on the integration of DFA and TRIZ methodologies for the design improvement. A household appliances consumer product was selected as a product case study. DFA analysis for the original design of product case study was conducted. The results than are compared to the new design proposed by the DFA methodology. Through TRIZ approach, trimming methods are used in order to develop the specific solution problem solving arise during the process of design improvement. The result than was analyzed using DFA analysis. TRIZ will booster up the design efficiency. Integration of DFA and TRIZ methodologies are able to improve the design efficiency by simplifying the parts.